What does the public want police to do during pandemics?: A national experiment - Nix, Justin (Criminology & public policy, 2021)
We administered a survey experiment to a national sample of 1068 U.S. adults in April 2020 to determine the factors that shape support for various policing tactics in the midst of the COVID-19 pandemic. Respondents were sharply divided in their views about pandemic policing tactics and were least supportive of policies that might limit public access to officers or reduce crime deterrence. Information about the health risks to officers, but not to inmates, significantly increased support for “precautionary” policing, but not for “social distance” policing. The information effect was modest, but may be larger if the information came from official sources and/or was communicated on multiple occasions. Other factors that are associated with attitudes toward pandemic policing include perceptions of procedural justice, altruistic fear, racial resentment, and authoritarianism.